Analysis of Quantum Teaching Model on Student’s Learning Outcomes - Mardawila Adha Anjeli; Martin Kustati; Nana Sepriyanti; Katryn Furmston; Cristina Parenti (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2024)
The Quantum Teaching Model is one approach learning innovative designed to improve? motivation and results Study participant. This study aims to analyze?? the influence of the Quantum Teaching model on results Study participant based on review literature. The research method used is review literature with collect data from various source trusted like a journal scientific, theses, and dissertations. Research results show that the Quantum Teaching model has influence positive and significant to results Study participant educate in various eye lessons. These findings indicate that the Quantum Teaching model can be alternative effective learning models to improve? quality education.